MORAL VALUE IN THE PATRIOT MOVIE AND RELATION WITH 18th CENTURY - Muhammad Ramdhan; Tenny Sudjatnika; Hasbi Assiddiqi (Universitas Islam Negeri Sunan Gunung Djati, 2022)
Movie is one of the media that has a significant impact on the dissemination of information and the transmission of messages to readers or the general public. This study aimed to discover moral value in